2011
DOI: 10.1007/s11085-011-9261-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Nickel/Tin Ratio on Cu Induced Surface Hot Shortness in Fe

Abstract: Surface hot shortness is of concern in scrap-based electric arc furnace (EAF) steelmaking. The excessive amount of residual copper (Cu) in the steel scrap enriches during the oxidation of the solid steel, and as a result a Cu-rich layer could form which causes inter-granular grain boundary cracking. Other residuals can also influence hot-shortness. Ni is known to improve the resistance to hot shortness whereas Sn is known to worsen it. In this paper, the mechanism through which nickel (Ni) counters the detrime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…It implies that copper is completely dissolved in iron at tempered temperature 700°C. It was reported 13,14 that the solubility limit of copper in steel increases with the addition of Ni to some extent which could contribute to this phenomenon. In addition, Cu precipitation will not occur during the tempering process due to the rapid cooling rate in air.…”
Section: Resultsmentioning
confidence: 96%
“…It implies that copper is completely dissolved in iron at tempered temperature 700°C. It was reported 13,14 that the solubility limit of copper in steel increases with the addition of Ni to some extent which could contribute to this phenomenon. In addition, Cu precipitation will not occur during the tempering process due to the rapid cooling rate in air.…”
Section: Resultsmentioning
confidence: 96%
“…The Cu and Ni maps of the oxidized Steel 2 sample, Figure 7, show that a continuous layer of Ni and Cu-rich Fe phase (referred as Fe(CuNi) phase) was formed along the scale/metal interface, and some Fe(CuNi) phase was occluded into the scale. This continuous layer of Fe(CuNi) phase was not seen in the steel containing Cu and Ni after short-time oxidations, suggesting a higher degree of residual element enrichment after long-time oxidation [18,19]. Meanwhile, large Fe oxides appeared close to the scale interface.
Figure 7. BSE-SEM image and elemental maps of the oxidized Steel 2 (0.15Cu-0.15Ni-0.03Sn).
…”
Section: Resultsmentioning
confidence: 99%
“…The major problem the Cu-rich liquid phase can cause is hot shortness when the liquid phase penetrates the Fe grain boundaries and leads to surface cracking during the subsequent hot rolling [11]. It has been found that Sn lowers the solubility of Cu in the steel and lowers the solidus temperature of the Cu-Fe alloy, promoting the formation of Cu liquid phase; meanwhile, the presence of Ni can counteract the effect of Sn by expanding the Cu solubility range in Fe [12][13][14][15][16][17][18][19]. In Imai et al's work [12,13], a mild steel containing 0.3 wt-% Cu (in wt pct) was subjected to oxidation for 2 h at 1000-1300°C followed by tensile testing with a strain of 40% at the oxidation temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors indicated that removing chlorined copper from steel is technically feasible [14]. Nickel alloying to steel increases both copper containing phases melting temperature and copper solution in austenite [15]. Increasing copper solubility in austenite prevents intergranular copper segregation and hot shortness.…”
mentioning
confidence: 99%